Study on the damage quantification model for exterior beam-column joints with headed bars in RC buildings based on the experimental data. (1st October 2022) - Chiu, Chien-Kuo; Kao, Yu-Chuan; Liao, I-Hsiang; Pratama Lays, David
Highlights: Formulas to estimate strengths of external B/C joints with headed bars. Models to estimate the shear distortion/width of external B/C joints with headed bars. A simplified procedure to control damage for external B/C joints with headed bars. Abstract: The main purpose of this work is to suggest formulas for estimating strengths external of beam-column (B/C) joints with headed bars in reinforced concrete (RC) buildings, with respect to the main failure modes, under cyclic loading. At first, this work collects relevant experimental data to confirm existing models and code formulas for the strength of external B/C joints with headed bars related to side-face blowout failure or concrete breakout failure. Furthermore, for the damage control, models to estimate the shear distortion and shear crack width of external B/C joints are proposed. Finally, a simplified procedure for controlling damage is developed.